Modification of Mordenite Characters by H2C2O4 and/or NaOH Treatments and Its Catalytic Activity Test in Hydrotreating of Pyrolyzed α-Cellulose - Triyono Triyono; Wega Trisunaryanti; Yessi Wydia Putri; Dyah Ayu Fatmawati; Uswatul Chasanah (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The research about modification of mordenite characteristics has been performed by H2C2O4 and/or NaOH treatments and catalytic activity tests in hydrotreating of pyrolyzed a-cellulose. Commercial mordenite (HSZ-604OA) as mordenite control (HM) immersed in 0.05, 0.5, and 1.0 M H2C2O4 at 70 °C for three hours resulting in HM-0.05, HM-0.5, and HM-1. The four mordenites were immersed in 0.1 M NaOH for 15 minutes resulting in BHM, BHM-0.05, BHM-0.5, and BHM-1. The catalysts obtained were analyzed by XRD, SAA, ICP, and acidity test. The catalytic activity of the mordenites was evaluated in hydrotreating of pyrolyzed a-cellulose using stainless steel reactor with an H2 gas flow rate of 20 mL.min−1 at 450 °C for two hours with a catalyst: feed weight ratio of 1:60. The liquid products obtained from the hydrotreating were analyzed using GC-MS. The research results showed that the H2C2O4 and/or NaOH treatment towards the mordenites increased Si/Al ratio and decreased crystallinity. The acidity of mordenites decreased along with the increase of the Si/Al ratio. The average pore diameter of BHM, BHM-0.05, BHM-0.5, and BHM-1 mordenites were 2.898; 3.005; 3.792; 7.429 nm, respectively. The BHM-0.5 mordenite showed the highest catalytic activity in generating liquid product (88.88 wt%) and selectivity toward propanol (4.87 wt%). The BHM-1 mordenite showed catalytic activity in generating liquid product (41.16 wt%) and selectivity toward ethanol (1.21 wt%) and 2-heptyne (4.36 wt%). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).